2011
DOI: 10.3390/en4101508
|View full text |Cite
|
Sign up to set email alerts
|

How Will Hydroelectric Power Generation Develop under Climate Change Scenarios? A Case Study in the Upper Danube Basin

Abstract: Climate change has a large impact on water resources and thus on hydropower. Hydroelectric power generation is closely linked to the regional hydrological situation of a watershed and reacts sensitively to changes in water quantity and seasonality. The development of hydroelectric power generation in the Upper Danube basin was modelled for two future decades, namely 2021-2030 and 2051-2060, using a special hydropower module coupled with the physically-based hydrological model PROMET. To cover a possible range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 48 publications
(71 reference statements)
2
41
0
Order By: Relevance
“…The mean annual precipitation in Munich reaches 930 mm with a summer precipitation peak [41]. Snow cover typically lasts for several weeks in winter, but with a decreasing trend in coverage duration and amount due to climate change [42,43].…”
Section: Gps Measurement Setup At the Dwd Test Site Munichmentioning
confidence: 99%
“…The mean annual precipitation in Munich reaches 930 mm with a summer precipitation peak [41]. Snow cover typically lasts for several weeks in winter, but with a decreasing trend in coverage duration and amount due to climate change [42,43].…”
Section: Gps Measurement Setup At the Dwd Test Site Munichmentioning
confidence: 99%
“…Their results showed that generation decreased by 1.3% and 19.7% under a warming-only scenario and a dry warming scenario, respectively. HP generation under the wet warming scenario increased by 5.8% [5] . Koch et al (2011) analysed the future development of hydropower productions in detail for the mountainous Upper Danube basin in Central Europe [6] .…”
Section: Introductionmentioning
confidence: 99%
“…HP generation under the wet warming scenario increased by 5.8% [5] . Koch et al (2011) analysed the future development of hydropower productions in detail for the mountainous Upper Danube basin in Central Europe [6] . Minville et al (2009) evaluated the impacts of and adaptation to climate change of the water resource management system of the Peribonka River, a Canadian water resource system exploited for hydropower [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the different sources of hydropower, small-scale hydroelectric power systems can be considered very interesting [1,2], but in order to make them economically feasible, they require low cost hydraulic and electric equipment. The strategy of pressure containment for leakage reduction…”
Section: Introductionmentioning
confidence: 99%